Research progress of hypoxia-inducible factor-1α and zinc in the mechanism of diabetic kidney disease - Qin, Wei; Nie, Ping; Hui, Xuejun; Chen, Fei; Hu, Xingbao; Shi, Wenjiao; Luo, Manyu; Li, Bing (Frontiers in Pharmacology, 2025)
Diabetic kidney disease is one of the common complications in diabetic patients and has gradually become an important pathogenic factor in chronic kidney disease. Therefore, studying the mechanisms of its occurrence and development is of great significance for the prevention and treatment of diabetic kidney disease. Some researchers have pointed out that there is a phenomenon of hypoxia in diabetic kidney tissue and believe that hypoxia-inducible factor-1α is closely related to the occurrence and progression of diabetic kidney disease. Additionally, the homeostasis of zinc plays a key role in the body’s adaptation to hypoxic environments. However, the specific relationship among these three factors remains unclear. This article provides a detailed review of the multiple roles of hypoxia-inducible factor-1α in the pathogenesis of diabetic kidney disease, including: regulating angiogenesis, increasing the expression of erythropoietin, modulating oxidative stress through the PI3K/AKT and HIF-1α/HO-1 pathways, promoting inflammatory cell infiltration and the release of inflammatory factors to induce inflammatory responses, facilitating epithelial-mesenchymal transition, pathological angiogenesis, and promoting the release of fibrotic factors, ultimately leading to renal fibrosis. Furthermore, HIF-1α also participates in the occurrence and development of diabetic kidney disease through mechanisms such as regulating apoptosis, inducing mitochondrial autophagy, and vascular calcification. At the same time, this article clarifies the regulatory role of the trace element zinc on hypoxia-inducible factor-1α in diabetic kidney disease. This article provides references and insights for further research on the pathogenesis and progression of diabetic kidney disease.